Infant Motor Development Predicts Sports Participation at Age 14 Years: Northern Finland Birth Cohort of 1966 - Ridgway, Charlotte L.; Ong, Ken K.; Tammelin, Tuija H.; Sharp, Stephen; Ekelund, Ulf; Jarvelin, Marjo-Riitta (PLOS ONE, 2009)
Background Motor proficiency is positively associated with physical activity levels. The aim of this study is to investigate associations between the timing of infant motor development and subsequent sports participation during adolescence. Methods Prospective observational study. The study population consisted of 9,009 individuals from the Northern Finland Birth Cohort 1966. Motor development was assessed by parental report at age 1 year, using age at walking with support and age at standing unaided. At follow up aged 14 years, data were collected on the school grade awarded for physical education (PE). Self report was used to collect information on the frequency of sports participation and number of different sports reported. Principal Findings Earlier infant motor development was associated with improved school PE grade, for age at walking supported (p<0.001) and standing unaided (p = <0.001). Earlier infant motor development, in terms of age at walking supported, was positively associated with the number of different sports reported (p = 0.003) and with a greater frequency of sports participation (p = 0.043). These associations were independent of gestational age and birth weight, as well as father's social class and body mass index at age 14 years. Conclusions Earlier infant motor development may predict higher levels of physical activity as indicated by higher school PE grade, participation in a greater number of different types of sports and increased frequency of sports participation. Identification of young children with slower motor development may allow early targeted interventions to improve motor skills and thereby increase physical activity in later life.